Unsupervised Cross-Subject Adaptation for Predicting Human Locomotion Intent - Zhang, Kuangen; Wang, Jing; de Silva, Clarence W.; Fu, Chenglong (IEEE transactions on neural systems and rehabilitation engineering, 2020)
Accurately predicting human locomotion intent is beneficial in controlling wearable robots and in assisting humans to walk smoothly on different terrains. Traditional methods for predicting human locomotion intent require collecting and labeling the human signals, and training specific classifiers for each new subject, which introduce a heavy burden on both the subject and the researcher. In addressing this issue, the present study liberates the subject and the researcher from labeling a large amount of data, by incorporating an unsupervised cross-subject adaptation method to predict the locomotion intent of a target subject whose signals are not labeled. The adaptation is realized by designing two classifiers to maximize the classification discrepancy and a feature generator to align the hidden features of the source and the target subjects to minimize the classification discrepancy. A neural network is trained by the labeled training set of source subjects and the unlabeled training set of target subjects. Then it is validated and tested on the validation set and the test set of target subjects. Experimental results in the leave-one-subject-out test indicate that the present method can classify the locomotion intent and activities of target subjects at the averaged accuracy of 93.60% and 94.59% on two public datasets. The present method increases the user-independence of the classifiers, but it has been evaluated only on the data of subjects without disabilities. The potential of the present method to predict the locomotion intent of subjects with disabilities and control the wearable robots will be evaluated in future work.